Magnetic integration of LTL filter with two LC-traps for grid-connected power converters - Li, Xiaoqiang (2020)
High-order inductor-traps-inductor (LTL) filters recently attracted a lot of research attentions in grid-connected converter applications due to their excellent harmonic attenuation ability, low cost, volume, and weight. However, more magnetic cores for trap inductors are required compared to conventional inductor-capacitor-inductor (LCL) filters. In order to further reduce the volume and weight of output power filter, this paper proposes a magnetic integrated LTL filter with two LC-traps. On the basis of conventional integrated LCL filters, the proposed method introduces a coupling winding wound on the central-limb of an EE-type magnetic core, and two equivalent trap inductors are introduced by the magnetic coupling between different windings. A step-by-step design guideline of the proposed magnetic integration method and the parameters design of LTL filters are also presented. The feasibility and effectiveness of the proposed method are finally verified by the experimental results.